Análise retrospectiva do planejamento virtual tridimensional sobre a acurácia no movimento maxilar nas cirurgias ortognáticas - Antonini, Fernando (2019)
The purpose of this study was to investigate accuracy of tridimensional virtual surgical planning over maxillary repositioning in bimaxillary orthognathic surgeries. Pre and postoperative CBCT images of one hundred patients were superimposed and linear distances between maxillary landmarks were measured in all 3 planes of space (x, y, and z axis). Virtual surgical planning and postoperative measurements were then compared. The patients were divided into five groups, according to the year in which virtual surgical planning (VSP) and surgical procedure was executed. Results show improved accuracy in maxillary position throughout the years, with more accurate results in patients that underwent bimaxillary orthognathic surgery in 2015, 2016 and 2017. Mean linear difference between planned and obtained results demonstrated more accurate results in horizontal direction, followed by transversal and vertical movements, with an overall average difference within 1mm observed in 51,3% of the subjects. Time seemed to play an important role in the accuracy of the maxilla in bimaxillary orthognathic surgery.